Efeito agudo de diferentes protocolos de aquecimento nos níveis de assimetria em aterrissagens - Costa, Victor Luzardo da (2024)
Lower limb asymmetries in jumping and landing tasks are discussed as being associated with performance, being a risk factor for injuries, and also aiding in clinical decision-making. However, assessing asymmetries in jumps is challenging because the magnitude of differences between limbs are usually small and highly variable among participants. This suggests that care is needed when establishing an asymmetry assessment protocol. In many studies, it is not clear whether there was a standardized warm-up before asymmetry measurements. Warm-up can influence force production, for example. By influencing force, it can affect jump height and consequently the magnitude of impact forces. Based on the hypothesis that warm-up affects force and power production, it is possible that a lack of control over warm-up could increase variability and cause confusion in interpreting results. In this study, we determined whether different pre-exercise warm-ups affect kinetic asymmetry measures in the lower limbs during jumping and landing tasks. For this purpose, we evaluated 28 adult futsal athletes (28 male, age 23 ± 3 years old, height 175.69 ± 5.37 cm, body mass 80.89 ± 14.38 kg) performing jumps and landings with or without prior warm-ups that promoted sport-specific stimuli or specific to jump tasks in which asymmetries were evaluated. Jump performance was evaluated considering jump height, reactive force index, peak and time to peak impact force on landing, and symmetry angle. When investigating effort demand, warm-up with sport-specific stimuli elicited higher intensity, depicted by a greater increase in heart rate and rate of perceived exertion than warm-up specific to jump tasks. There was no difference in jump height and reactive force index before and after different warm-up protocols. Regarding kinetic variables and asymmetries, both in pre- and post-comparisons and between interventions, warm-ups that promoted sport-specific stimuli and specific to jump tasks showed no differences in kinetic variables and angle of symmetry. In conclusion, different warm-up protocols did not influence jump and landing kinetics, including asymmetry measures.